A LEFT ATRIAL GIGANTIC MIXOMA ON BACKGROUND OF MITRAL VALVE DYSPLASIA - S. L. Dzemeshkevitch; Yu. V. Frolova; L. I. Rizun; A. S. Dzemeshkevitch; V. V. Raskin; S. V. Fedulova; A. N. Dzeranova; S. A. Mironovich (Российский кардиологический журнал)
Aim. To demonstrate a clinical case of mixoma with mitral regurgitation Material and methods. The operation performed: excision of voluminous formation of the left atrium, mitral valve plastic with supporting ring Edwards Lifescience 32, interatrial septum plastic with the VAsCUTEC patch under conditions of artificial circulation and pharmacy-cold cardioplegy. Results. Complete myxoma excision, absence of mitral regurgitation afteroperation. Conclusion. Complete myxoma excision and mitral regurgitation correction lead to a good clinical result.A LEFT ATRIAL GIGANTIC MIXOMA ON BACKGROUND OF MITRAL VALVE DYSPLASIADzemeshkevitch S. L., Frolova Yu.V., Rizun L. I., Dzemeshkevitch A. S., Raskin V. V., Fedulova S. V., Dzeranova A. N., Mironovich S. A.